Assessing the combustibility of claddings: A comparative study of the modified cone calorimeter method and cylindrical furnace test. (10th May 2021) - Nguyen, Kate; Kim, Nam Kyeun; Bhattacharyya, Debes; Mouritz, Adrian
Summary: A cone calorimeter, a standard device to measure the fire reaction properties of materials, is modified in this study to investigate its potential to replace the cylindrical furnace test method to assess the combustibility of cladding materials used in buildings. The modification allows cladding materials to be evaluated under conditions closer to their end‐use configuration than the current testing condition in the cylindrical furnace test. In addition, the modified cone calorimeter method provides more quantitative data on the fire reaction properties of the cladding materials compared to the passed/failed indicator in the cylindrical furnace test. Comparative studies between modified cone calorimeter and cylindrical furnace test results for four types of cladding with different combustibility properties are performed. The surface temperature, time‐to‐ignition, and flaming duration values measured for the claddings using the two test methods are similar, leading to the same classification based on AS 1530.1 standard. Other fire reaction properties of the claddings can be measured using the modified cone calorimeter method, which is not possible with the cylindrical furnace test, including mass loss rate, heat release rate, and smoke production, which are particularly dependent on the formation of a ceramic‐like carbonaceous layer of tested samples.